One-pot synthesis and aqueous solution properties of pH-responsive schizophrenic diblock copolymer nanoparticles prepared via RAFT aqueous dispersion polymerization. Issue 40 (29th September 2021) - North, S. M.; Armes, S. P.
Abstract : Well-defined doubly pH-responsive schizophrenic diblock copolymer nanoparticles with tunable isoelectric points are prepared via RAFT aqueous dispersion polymerization using an efficient one-pot protocol. Abstract : Schizophrenic diblock copolymers can form two types of nanoparticles in aqueous solution, with such self-assembly typically being driven by a change in solution temperature, solution pH or salt concentration. In the present study, we report the first wholly aqueous one-pot synthesis of a doubly pH-responsive schizophrenic diblock copolymer. This is achieved using RAFT aqueous dispersion polymerization, which is an example of polymerization-induced self-assembly (PISA). First, 2-(diethylamino)ethyl methacrylate (DEA) is homopolymerized in its protonated form at pH 2 to produce a cationic polyelectrolytic precursor. Subsequently, the RAFT aqueous dispersion polymerization of 2-carboxyethyl acrylate (CEA) is conducted to produce sterically-stabilized diblock copolymer nanoparticles in which the cationic PDEA block acts as the hydrophilic stabilizer block and the neutral PCEA block forms the hydrophobic core. On addition of sufficient NaOH, the PCEA becomes highly anionic at pH 10 and hence acts as a stabilizer block while the deprotonated PDEA block forms the hydrophobic core. Characterizing such polyampholytes via aqueous gel permeation chromatography is challenging. Thus a selective methylation protocol was developed to esterify the anionic carboxylate groups in the PCEA block to enable GPC analysis using THF as an eluent. However, optimization of the reaction conditions was required because using too large an excess of the trimethylsilyldiazomethane reagent led to unwanted quaternization of the tertiary amine groups on the PDEA block, which prevented meaningful GPC analysis. The aqueous self-assembly behaviour of a series of PDEA–PCEA diblock copolymers was examined using transmission electron microscopy, dynamic light scattering, 1 H NMR spectroscopy and aqueous electrophoresis.